The genome sequence of a tachinid fly, Dexiosoma caninum (Fabricius, 1781) [version 1; peer review: 2 approved] - Olga Sivell; Chris Raper; Ryan Mitchell (Wellcome Open Research, 2024)
We present a genome assembly from a female tachinid fly Dexiosoma caninum (Arthropoda; Insecta; Diptera; Tachinidae). The genome sequence has a total length of 517.10 megabases. Most of the assembly is scaffolded into 6 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 18.7 kilobases in length.